Transdermal Delivery of Active Principles with Pulsed RF Contact Diathermy - A Narrative Review - Gallamini, Michele; Bernabei, Gianluca; Pecchioli, Eugenio (International Journal of Innovative Research in Medical Science, 2021)
The transdermal delivery of drugs and, in more general terms, of active principles can be performed by iontophoresis and/or by electroporation. The advantages of a local treatment vs. other drugs intake methods are well known as it reduces the systemic involvement and therefore the systemic contraindications. To perform the treatment exploiting the electroporation effect there is nowadays a specific variant of a known medical device used in physiotherapy: the Medium Frequency Resistive/Capacitive contact Diathermy. The adoption of a power control exploiting Pulse Width Modulation of the applied current adds to the device also this capability of great potential in rehabilitation and aesthetic medicine treatments. The theoretic approach is discussed and applications suggestions are being given.